2020
DOI: 10.1097/hcr.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home-Based Cardiac Rehabilitation in a Lower-Middle Income Country

Abstract: The study received no funding. All authors declare no conflicts of interest. Word count: 2909. 4 tables, 1 figure, 27 references, 1 appendix. Home-based Cardiac Rehabilitation in a Lower middle income country: a controlled trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“… Physical activity (exercise part of specific questionnaire designed by Kamrani F et al) (2 months) pre-CR 16.58 ± 5.10; post-CR 26.00 ± 3.59; pre-UC 17.20 ± 4.34; post-UC 16.94 ± 4.84; Significant difference within CR ( p < 0.001) group following intervention. Uddin 2019, 69 Bangladesh, SEA N = 142; mean age 54.0 years; 7.0% female; 0.0% HF and/or non-ACS patients included Quasi-randomised controlled trial with 2 parallel arms; 1 site. UC- Y (The standard of care for cardiovascular patients in Bangladesh includes conventional hospital discharge care along with medication adjustment and routine follow-up advices by cardiologists); AC comparison-No ITT: y Functional Capacity (VO 2 max ) (mL/Kg/min) (6 months) ∫ post-CR 35.70 ± 10.12; post-UC 29.13 ± 12.95; Significant difference between groups ( p < 0.01) post-intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Physical activity (exercise part of specific questionnaire designed by Kamrani F et al) (2 months) pre-CR 16.58 ± 5.10; post-CR 26.00 ± 3.59; pre-UC 17.20 ± 4.34; post-UC 16.94 ± 4.84; Significant difference within CR ( p < 0.001) group following intervention. Uddin 2019, 69 Bangladesh, SEA N = 142; mean age 54.0 years; 7.0% female; 0.0% HF and/or non-ACS patients included Quasi-randomised controlled trial with 2 parallel arms; 1 site. UC- Y (The standard of care for cardiovascular patients in Bangladesh includes conventional hospital discharge care along with medication adjustment and routine follow-up advices by cardiologists); AC comparison-No ITT: y Functional Capacity (VO 2 max ) (mL/Kg/min) (6 months) ∫ post-CR 35.70 ± 10.12; post-UC 29.13 ± 12.95; Significant difference between groups ( p < 0.01) post-intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Theory: no. Uddin 2019, 69 Bangladesh 13 sessions (first session face to face then monthly follow up by phone calls for 12 months [face-to-face & remote both]); 45 min long for the 1st session Hospital and at home; II; Technology-Yes (12 phone calls each per month); physician, physiotherapist; Participants in intervention group were advised to exercise at least 30 min/day, including a 5-min warm-up and a 5-min cool-down, and need to be completed 4 days/week. Exercise was prescribed at an intensity of 11 to 13 on the Borg scale of rating of perceived exertion.…”
Section: Resultsmentioning
confidence: 99%
“…From 2010, IchrI introduced an exercise-based and education-based multidisciplinary cardiac rehabilitation programme for patients after cardiac surgery, consisting of a 30-min group exercise programme supported with a leaflet on sternum protection containing advice that can be followed at home. a single-centre, quasi-randomized controlled trial indicated that this cardiac rehabilitation programme was feasible and had potential benefits in terms of coronary heart disease risk factors, health-related quality of life, mental wellbeing and exercise capacity 90 . Following a 12-month clinical fellowship in Denmark and the uK in 2015, Jamal uddin (a senior physiotherapist) started a comprehensive cardiac rehabilitation programme at the IchrI.…”
Section: Box 6 | Case Example: Cardiac Rehabilitation In Bangladeshmentioning
confidence: 99%
“…Furthermore, this model could be extended to include other patient groups with, for example, transient ischaemic attack, mild stroke or peripheral vascular disease. Box 6 provides a case example of the development of cardiac rehabilitation in the LMIC setting of Bangladesh 90 . Expansion of cardiac rehabilitation services is urgently needed to mitigate the epidemic of cardiovascular diseases in LMICs.…”
Section: Inclusivitymentioning
confidence: 99%
“…A study that was published in the Journal of Cardiopulmonary Rehabilitation and Prevention, has compared usual care with HBCR plus usual care; greater reductions in IHD major risk factors and an improvement in the quality of life have been demonstrated in participants who had received HBCR. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%